Benchmarking rehabilitation practice in the intensive care unit. (February 2015) - Knott, Anna; Stevenson, Matt; Harlow, Stephanie KM
Introduction: Early rehabilitation in critically ill patients has been demonstrated to be safe and is associated with many positive outcomes. Despite this, there are inconsistencies in the early active rehabilitation that patients receive on intensive care units. The aims of this study were to quantify the amount of active rehabilitation provided for patients in a District General Hospital intensive care unit and to identify specific barriers encountered. Methods: Data were collected over a six-week period during March and April 2013. All patients admitted to the intensive care unit at St Peter's Hospital for more than 48 h were included. For every treatment session, the treating physiotherapist recorded what type of treatment took place. Treatments were classified as either non-active or active rehabilitation. Non-active rehabilitation included chest physiotherapy, passive range of movement exercises and hoisting to a chair. Active rehabilitation was defined as any treatment including active/active-assisted exercises, sitting on the edge of the bed, sitting to standing, standing transfers, marching on the spot or ambulation. Classification of rehabilitation was based upon internationally agreed intensive care unit activity codes and definitions. All barriers to active rehabilitation were also recorded. Results: The study included 35 patients with a total of 194 physiotherapy treatment sessions. Active rehabilitation was included in 51% of all treatment sessions. The median time to commencing active rehabilitation from intensive care unit admission was 3 days (range 3–42 [IQR 3–7]). The most frequent barriers to active rehabilitation were sedation and endotracheal tubes, which together accounted for 50% of the total barriers. Conclusion: The study provides useful benchmarking of current rehabilitation activity in a District General Hospital intensive care unit and highlights the most common barriers encountered to active rehabilitation. Longer duration studies incorporating larger sample sizes are warranted. Future studies should utilise the internationally agreed intensive care unit activity codes to improve comparability.